Light color importance for circadian entrainment in a diurnal (Octodon degus) and a nocturnal (Rattus norvegicus) rodent - Maria Angeles Bonmati-Carrion (Nature Portfolio, 2017)
Abstract The central circadian pacemaker (Suprachiasmatic Nuclei, SCN) maintains the phase relationship with the external world thanks to the light/dark cycle. Light intensity, spectra, and timing are important for SCN synchronisation. Exposure to blue-light at night leads to circadian misalignment that could be avoided by using less circadian-disruptive wavelengths. This study tests the capacity of a diurnal Octodon degus and nocturnal Rattus norvegicus to synchronise to different nocturnal lights. Animals were subjected to combined red-green-blue lights (RGB) during the day and to: darkness; red light (R); combined red-green LED (RG) lights; and combined red-green-violet LED (RGV) lights during the night. Activity rhythms free-ran in rats under a RGB:RG cycle and became arrhythmic under RGB:RGV. Degus remained synchronised, despite the fact that day and night-time lighting systems differed only in spectra, but not in intensity. For degus SCN c-Fos activation by light was stronger with RGB-light than with RGV. This could be relevant for developing lighting that reduces the disruptive effects of nocturnal light in humans, without compromising chromaticity.